REGENERASIPROTOPLAS TANAMAN TERUNG DAN KETAHANAN REGENERAN TERHADAPPENYAKIT BAKTERILAYU - Ali Husni (BERITA BIOLOGI, 2005)
Protoplasts regeneration was studied on 3 cultivars of eggplant (pupel, green, ang white fruits) and the regenerant were tested for their resistance to bacterial wilt. The researh was conducted in different steps, including protoplast isolation, protoplast purification, protoplast culture, cell suspention dilution, shoot regeneration, plantlet aclimatization, and testing for the resistant to bacterial wilt. Observations were made for protoplast number of each cultivar, protoplast cell wal formation, cell division, number of cell colony, microcalli, and shoot, percent of plantlet survival, in acclimatization, and the resistance of regenerants to bacterial wilt. Data was analized by calculating the average, percentage, and standart deviation. Results show that the combination of 0.5% cellulase Onozuka RS, 0.5% macerozyme R-10, 0.05% MES, and 9,1% mannitol in CPW solution was able to isolateds alot of sprotoplast (10 ) in each cultivars. The first culture incubation with out lighty in both (KM8P and VKM) media and reach which 0,2 mg/1 2,4-D, 0,5 mg/1 zeathin, 1 mg/1 IAA, promoted the formation of cell wall and cell division developed to microcalli. Regeneration media of MS, applied with vitamin MW, 0,1 mg/1 NAA, and 2 mg/1 zeathine produced 13 shoots.. From 21 regenerants acclimatized only 15 regenerants survive. There were differences among the regenerants in their resistance to bacterial wilt,3 regenerants resistant, 2 regenerant recovery (tolerant) and 10 regenerants were susceptibel.